ChemInform Abstract: Metal‐Free C—H Arylation of Aminoheterocycles with Arylhydrazines. Issue 43 (7th October 2016) - Taniguchi, Toshihide; Imoto, Mitsutaka; Takeda, Motonori; Matsumoto, Fukashi; Nakai, Takeo; Mihara, Masatoshi; Mizuno, Takumi; Nomoto, Akihiro; Ogawa, Akiya
Abstract: Heterocyclic amines and diamine (Ib) are successfully arylated under atmospheric conditions in the presence of an inexpensive base.